GLP-1/GIP Agonist as an Intriguing and Ultimate Remedy for Combating Alzheimer's Disease through its Supporting DPP4 Inhibitors: A Review - Abubakar, Mohammad; Nama, Lokesh; Ansari, Mohammad A.; Ansari, Mohammad Mazharuddin; Bhardwaj, Shivani; Daksh, Rajni; Syamala, Katta L. V.; Jamadade, Mohini Santosh; Chhabra, Vishal; Kumar, Dileep; Kumar, Nitesh (Current Topics in Medicinal Chemistry, 2024)
Background: Alzheimer's disease (AD) is a widespread neurological illness in the elderly, which impacted about 50 million people globally in 2020. Type 2 diabetes has been identified as a risk factor. Insulin and incretins are substances that have various impacts on neurodegenerative processes. Preclinical research has shown that GLP-1 receptor agonists decrease neuroinflammation, tau phosphorylation, amyloid deposition, synaptic function, and memory formation. Phase 2 and 3 studies are now occurring in Alzheimer's disease populations. In this article, we present a detailed assessment of the therapeutic potential of GLP-1 analogues and DPP4 inhibitors in Alzheimer's disease. Aim: This study aimed to gain insight into how GLP-1 analogues and associated antagonists of DPP4 safeguard against AD. Methods: This study uses terms from search engines, such as Scopus, PubMed, and Google Scholar, to explore the role, function, and treatment options of the GLP-1 analogue for AD. Results: The review suggested that GLP-1 analogues may be useful for treating AD because they have been linked to anti-inflammatory, neurotrophic, and neuroprotective characteristics. Throughout this review, we discuss the underlying causes of AD and how GLP signaling functions. Conclusion: With a focus on AD, the molecular and pharmacological effects of a few GLP-1/GIP analogs, both synthetic and natural, as well as DPP4 inhibitors, have been mentioned, which are in the preclinical and clinical studies. This has been demonstrated to improve cognitive function in Alzheimer's patients.
Keywords: Incretins